2021
DOI: 10.1186/s40168-020-00944-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-dosage ozonation in gas-phase biofilter promotes community diversity and robustness

Abstract: Background The ozonation of biofilters is known to alleviate clogging and pressure drop issues while maintaining removal performances in biofiltration systems treating gaseous volatile organic compounds (VOCs). The effects of ozone on the biofilter microbiome in terms of biodiversity, community structure, metabolic abilities, and dominant taxa correlated with performance remain largely unknown. Methods This study investigated two biofilters treatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Correlation-based network analysis offers new insights into microbial community structure and its co-occurrence patterns, showing ecological interactions ( Yeung et al, 2021 ). Modularity is an important indicator of ecosystem stability and resilience ( Sharaf et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation-based network analysis offers new insights into microbial community structure and its co-occurrence patterns, showing ecological interactions ( Yeung et al, 2021 ). Modularity is an important indicator of ecosystem stability and resilience ( Sharaf et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha and Beta diversity metrics were evaluated by QIIME2 version 2020.2 [ 15 , 16 ], and differential analysis among groups on alpha diversity metrics was processed by one-way ANOVA. Linear discriminant analysis (LDA) effect size (LEfSe) analyses were performed using the LEfSe tool [ 17 ], and LDA log-score threshold was set to 3.0 [ 18 , 19 ]. The metagenomes and function of the intestinal microbiota were analyzed using the PICRUSt2 ( accessed on 1 August 2022) and the differences in KEGG pathways between groups were analyzed by using STAMP (version 2.1.3) [ 20 ], the significance of the difference in function abundance between groups was evaluated by one-way ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…The biomass produced by UV-BTF was slightly lower than the single BTF, which was attributed to the effect of UV-generated ozone on microorganisms, and the ozone concentration in the present study is shown in Supplementary Figure S3. Yeung et al (2021) showed that low doses of ozone can significantly improve the overall performance of biofilters by forming a stronger microbiome and improving clogging problems. Therefore, the amount of biomass alone was not Frontiers in Environmental Science frontiersin.org enough to describe the role of microorganisms in the system, and information on the structure of the microbial community was also needed.…”
Section: Carbon Balance Analysis For Rectormentioning
confidence: 99%